Mind the gap: Comparing the net value of geothermal, wind, solar, and solar+storage in the Western United States. (March 2023) - Bolinger, Mark; Millstein, Dev; Gorman, Will; Dobson, Patrick; Jeong, Seongeun
Abstract: Studies show that a diverse portfolio of zero-carbon resources will be needed to decarbonize the U.S. electricity sector, and that high capacity factor resources like geothermal will become particularly important in later stages of decarbonization as the capacity contribution of variable, weather-dependent resources like wind and solar declines with increasing market penetration. Yet while wind, solar, and—more recently—storage have all seen significant U.S. deployment in recent years, deployment of new geothermal plants has barely budged over the same period. We explain this disparity in historical deployment by analyzing empirical price data from power purchase agreements (PPAs) and wholesale energy and capacity markets, which demonstrate that geothermal has historically offered a lower "net value" (i.e., wholesale market value minus PPA price) than these other resources. Looking ahead through 2026, continued growth in the market share of wind, solar, and storage should improve geothermal's relative market value, yet likely not by enough to overcome the persistent cost gap between geothermal and these other, lower-cost resources. In the face of this challenging market outlook, policy intervention and continued R&D investments may be warranted to sustain a vibrant geothermal industry that stands ready to contribute to the late stages of decarbonization.